2013
DOI: 10.1016/j.cplett.2013.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interactions between fullerene C60 and ionic liquids

Abstract: a b s t r a c tStructural and energetic aspects of solvation of fullerene C 60 in ionic liquids at room temperature were analyzed by using atomistic molecular dynamics simulations. Ethylammonium Nitrate (EAN) and 1-Butyl-3-Methylimidazolium Tetrafluoroborate (BMIMBF4) ionic liquids were conveniently chosen for presenting different polarities. Analysis of the spatial distribution of the ionic liquid revealed different patterns for the solvation of C 60 . Energetics indicated that the presence of C 60 weakened t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 34 publications
3
63
2
Order By: Relevance
“…Significant progress has been made in the application of molecular dynamics simulations to similar systems [19,20,30,31]. The initial configuration of each system consisted of an agglomerate species of C 60 .…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Significant progress has been made in the application of molecular dynamics simulations to similar systems [19,20,30,31]. The initial configuration of each system consisted of an agglomerate species of C 60 .…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Maciel et al also found that in [C 4 mim][BF 4 ] the IL-cation nears the surface of C 60 described using an extensive MD simulation. 20 To make insight into the structure of ILs around the C 60 more deeply, the RDF profiles of nitrogen-2 atom in [C n mim]…”
Section: Resultsmentioning
confidence: 99%
“…16 Moreover, contemporary studies indicate that their "greenness" depends strongly on their structures, 17 and that these intrinsic properties also make ILs superior as ideal dispersing media for CNPs. [18][19][20] Accordingly, it is presently unclear whether CNPs produced in the presence of ILs will directly correspond to CNP-IL complexes that will be found in the environment. Furthermore, though there is no direct evidence for ILs being found in the environment, recent efforts to prepare for possible release suggest that ILs can present a low to high risk to human and ecological species.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these works are based on the applications of classic Molecular Dynamics methods (MD). 4,5,6,7,8,9,10,11 Nevertheless, Density Functional Theory (DFT) simulations 12 or quantitative structure properties relationship (QSPR) 13 studies have been also published. Among the new alternatives studied for C 60 dispersion in solvents, the recent works by Chaban et al 5 …”
Section: Introductionmentioning
confidence: 98%